2016
DOI: 10.1194/jlr.p068379
|View full text |Cite
|
Sign up to set email alerts
|

Increasing insulin resistance accentuates the effect of triglyceride-associated loci on serum triglycerides during 5 years

Abstract: A high level of circulating triglycerides is a risk factor for type 2 diabetes, myocardial infarction, ischemic heart disease, and all-cause mortality (1-4). A recent Mendelian randomization study supports a causal effect of triglycerides on coronary heart disease risk (5). Regulation of blood levels of triglycerides involves a complex interplay implicating both the liver and pancreas. Some of the important players in this regard are body adiposity, insulin resistance, and glucose homeostasis (6). In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It was also observed in the Danish Inter99 cohort, which included 3,474 non-diabetic individuals, that over a period of 5 years a wGRS comprised of 39 genetic variants was associated with an increase in serum triglyceride levels and change in insulin resistance acted as an effect modifier. Although the results indicated that increased insulin resistance accentuated the effect of wGRS, no causality can be deduced from these findings [38].…”
Section: Discussionmentioning
confidence: 77%
“…It was also observed in the Danish Inter99 cohort, which included 3,474 non-diabetic individuals, that over a period of 5 years a wGRS comprised of 39 genetic variants was associated with an increase in serum triglyceride levels and change in insulin resistance acted as an effect modifier. Although the results indicated that increased insulin resistance accentuated the effect of wGRS, no causality can be deduced from these findings [38].…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, incorporating a ketogenic diet may unlock greater metabolic efficiency in the human body (29). High serum TC and TG are closely associated with many health problems including atherosclerosis, type 2 diabetes and coronary heart disease (44,45). Lei et al found that a high-fat diet for 11 weeks exhibited significantly higher TC and TG levels compared to non-obese mice on a normal diet (46).…”
Section: Effects Of Dietary Intervention On Antioxidant Capacity Of L...mentioning
confidence: 99%